2014
DOI: 10.1093/mnras/stu1295
|View full text |Cite
|
Sign up to set email alerts
|

High proper motion objects from the UKIDSS Galactic plane survey

Abstract: The UKIDSS Galactic Plane Survey (GPS) began in 2005 as a 7 year effort to survey ∼1800 deg 2 of the northern Galactic plane in the J, H, and K passbands. The survey included a second epoch of K band data, with a baseline of 2 to 8 years, for the purpose of investigating variability and measuring proper motions. We have calculated proper motions for 167 Million sources in a 900 deg 2 area located at l > 60 • in order to search for new high proper motion objects. Visual inspection has verified 617 high proper m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Proper motions have enabled searches to distinguish ultracool dwarfs from distant luminous red objects, such as giants and galaxies (e.g., Kirkpatrick et al 2000;Theissen et al 2016Theissen et al , 2017, and to determine whether individual discoveries are members of starforming regions (e.g., Lodieu et al 2007aLodieu et al , 2012a. Proper motions have helped to find objects in crowded areas of the sky, such as the Galactic plane (e.g., Luhman 2013; Smith et al 2014a), and to identify ultracool dwarfs with atypical colors that were missed by color cuts used in photometry-only searches (e.g., Kirkpatrick et al 2010). Several studies have found clear evidence for dynamically cold (slow-moving) and hot (fast-moving) populations of ultracool dwarfs that are consistent with thin disk and thick disk/halo populations (e.g., Faherty et al 2009;Schmidt et al 2010;Dupuy & Liu 2012), implying that ultracool dwarfs form in the same manner as hotter stars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper motions have enabled searches to distinguish ultracool dwarfs from distant luminous red objects, such as giants and galaxies (e.g., Kirkpatrick et al 2000;Theissen et al 2016Theissen et al , 2017, and to determine whether individual discoveries are members of starforming regions (e.g., Lodieu et al 2007aLodieu et al , 2012a. Proper motions have helped to find objects in crowded areas of the sky, such as the Galactic plane (e.g., Luhman 2013; Smith et al 2014a), and to identify ultracool dwarfs with atypical colors that were missed by color cuts used in photometry-only searches (e.g., Kirkpatrick et al 2010). Several studies have found clear evidence for dynamically cold (slow-moving) and hot (fast-moving) populations of ultracool dwarfs that are consistent with thin disk and thick disk/halo populations (e.g., Faherty et al 2009;Schmidt et al 2010;Dupuy & Liu 2012), implying that ultracool dwarfs form in the same manner as hotter stars.…”
Section: Introductionmentioning
confidence: 99%
“…Proper motions measured from the large surveys have enabled us to identify the substellar members of nearby young moving groups (e.g., Gagné et al 2015cGagné et al , 2015bFaherty et al 2016;Liu et al 2016), a population crucial to our understanding of brown dwarf evolution over their first few hundred million years. Proper motions from large catalogs have also identified wide, comoving companions to higher-mass stars, whose ages and metallicities can more easily be determined (e.g., Luhman et al 2012;Burningham et al 2013;Zhang et al 2013;Smith et al 2014a), making the ultracool companions important benchmarks for constraining atmospheric and evolutionary models.…”
Section: Introductionmentioning
confidence: 99%
“…With the aims of detecting rarely seen high amplitude infrared variable stars and measuring proper motions, a second epoch of K photometry was obtained for most of the UGPS area with a time baseline of 1.8 to 8 yrs. New high proper motion discoveries were presented by Smith et al (2014). Initial discoveries from the variable star search were presented in Paper I of this series (Contreras Peña et al 2014) which described 45 stars from the 5th and 7th UGPS data releases with variations above 1 mag in K. These near infrared surveys have been complemented by two-epoch mid-infrared searches of data from the Spitzer Space Telescope (Werner et al 2004) and the Wide-field Infrared Survey Explorer (Wright et al 2010), see Scholz, Froebrich & Wood (2013); Antoniucci et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Others used several of those surveys to identify new candidates (Aberasturi et al 2011;Scholz et al 2012) or added a second epoch of K-band astrometry, such as the UKIDSS Galactic Plane Survey (GPS; Lucas et al 2008), in which a new T5 dwarf and several other L and T dwarf candidates were recently discovered in the galactic plane (Smith et al 2014).…”
Section: Introductionmentioning
confidence: 99%